FOREIGN INVESTOR AND MARKET VOLATILITY: EVIDENCE ON INDONESIA STOCK MARKET - Kristian, Michelle; Adiwena, Stevanus; Laksana, Yohanes Bayu (International Journal of Application on Economics and Business, 2023)
Indonesia as the fourth largest country in the world as well as its status as emerging country has attracted many investors, especially foreign investors. Previous studies still debating whether these foreign investors are giving significant effect on Indonesia stock market volatility. Our study found that there is evidence on how foreign investors affecting the stock market. Evidence found suggest that foreign trading activity gives significant effect on Indonesia stock market volatility. Another evidence suggested that as market capitalization increases, trading volume will increase as well. However, our findings found that the percentage of foreign investor ownership does not give any significant effect towards market volatility.